Peniphenylanes A–G from the Deep-Sea-Derived Fungus Penicillium fellutanum HDN14-323 - Zhang, Zhenzhen; Guo, Wenqiang; He, Xueqian; Che, Qian; Zhu, Tianjiao; Gu, Qianqun; Li, Dehai (Planta Medica, 2016)
Seven new 6-methylsaligenin derivatives, including the trimeric peniphenylanes A–B (1–2) and dimeric peniphenylanes C–G (3–7), together with four known biogenetically related compounds (8–11) were discovered from the extract of the deep-sea-derived fungus Penicillium fellutanum HDN14-323. The structures of the new compounds were established through extensive analysis. Their cytotoxic activity against HeLa, HL-60, and HCT-116 cell lines was evaluated, with compound 4 exhibiting the best activity against the HeLa cell line (IC50 = 9.3 µM).
Keywords: Penicillium fellutanum; Trichocomaceae; 6-methylsaligenin; peniphenylanes; deep-sea-derived fungus; cytotoxic activity